If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5(2c + -3) = 2c + 5 Reorder the terms: 5(-3 + 2c) = 2c + 5 (-3 * 5 + 2c * 5) = 2c + 5 (-15 + 10c) = 2c + 5 Reorder the terms: -15 + 10c = 5 + 2c Solving -15 + 10c = 5 + 2c Solving for variable 'c'. Move all terms containing c to the left, all other terms to the right. Add '-2c' to each side of the equation. -15 + 10c + -2c = 5 + 2c + -2c Combine like terms: 10c + -2c = 8c -15 + 8c = 5 + 2c + -2c Combine like terms: 2c + -2c = 0 -15 + 8c = 5 + 0 -15 + 8c = 5 Add '15' to each side of the equation. -15 + 15 + 8c = 5 + 15 Combine like terms: -15 + 15 = 0 0 + 8c = 5 + 15 8c = 5 + 15 Combine like terms: 5 + 15 = 20 8c = 20 Divide each side by '8'. c = 2.5 Simplifying c = 2.5
| 8n=n+42 | | X+Y=231 | | x+2=-2x-14 | | 16x-92=180 | | 5=x+31 | | -4-(-4)/3-6 | | 10y=-8 | | -324=27s | | (14x+7)-(-3x+2)= | | 4(3z-3)=9z-7 | | X+11x=156 | | 4x+8(-3x-3)=3 | | 12*48= | | 3-2/6-3 | | 25x^3y^4+50x^3y^4-75x^2y^3=0 | | x^2=2x-21 | | 3/4k-28=4 | | (12*4)+16= | | 3(2p+7)=82+x | | 8(-9+3)=6(-9+1) | | 9x+63=180 | | 4x-2(-2x-4)=3x-10+5x | | 1-(-1)/-6-4 | | 13x=16y+1 | | K-311=203 | | d-3.4=-9.3 | | 2x^6+4x^4+8x=0 | | 8(x+3)=6(x+1) | | -15=-3v | | 3/6-2/2 | | 4y=2(y-5)-w | | D+191=953 |